MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA DENGAN METODE THINK PAIR SHARE (TPS) PADA SISWA VIII A DI SMPN 4 TAPUNG HILIR - Fevi Sumarya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to apply the Think Pair Share (TPS) Method to improve the learning outcomes of science in class VIII A students at SMPN 4 Tapung Hilir. Learning outcomes give a very important role for students in improving achievement to be more beneficial. Learning outcomes can be seen from cognitive abilities, affective, psychomotor. This research uses classroom action research methods. The research instrument consisted of tests and non-tests. the results of research and discussion shows the Think Pair Share method can improve student learning outcomes in science subjects. This can be seen in cycle I students who reached 82% while students who did not complete reached 18% and the Think Pair Share method can also increase student enthusiasm in learning so that the classroom atmosphere when teaching and learning process becomes more lively. It is recommended to science teachers who will try the TPS method by adding variations and do not make the achievement of teaching materials and time as the main benchmark but make student understanding as the main goal of the success of group discussions and other researchers can investigate further with deeper discussion for example in the field other studies or other levels of education.